Crashworthy Structure Analysis of Indonesia's First High-speed Train Trailer Made from Aluminum Extrusion - Syaifudin, Achmad; Muh Luqman, Khakim (Journal of Engineering and Technological Sciences, 2025)
In the development of high-speed trains, evaluating the crashworthiness of passenger car structures is essential, particularly in the vestibule area which designed to absorb impact energy. When constructed entirely from aluminum extrusion, the vestibule exhibits high stiffness and uncontrolled energy absorption, resulting in excessive deceleration during collisions. This study investigates the crashworthiness of the vestibule structure in Indonesian high-speed train trailers, referencing EN 15227/SNI 8826 and 49 CFR 238 standards. A numerical analysis was conducted using ANSYS LS-DYNA, examining four structural configurations: a full aluminum extrusion model referred to the rear end structure of the HST locomotive, and three alternatives incorporating structural beams in the roof, floor, and modified floor areas. Simulations involved train collisions with a rigid wall at regulated speeds, using aluminum 6005A-T6 modeled with the Johnson-Cook material model to account for high strain rates. Results showed that the full aluminum design produced excessive deceleration and failed to meet EN 15227/SNI 8826 criteria. In contrast, the modified floor frame design achieved the lowest crash force and deceleration, controlled energy absorption, no survival space reduction, and compliance with EN 15227/SNI 8826, though it did not meet 49 CFR 238 deceleration limits due to full vestibule deformation. These findings offer valuable insights for manufacturers seeking to enhance the crashworthiness of high-speed train passenger cars.